EFFECT OF CONCENTRATION VARIATION OF SORBITOL AND SUCROSE IN THE SOLUBILITY OF ZIKA VIRUS MULTI-EPITOPE ENVELOPE PROTEIN IN Escherichia coli BL21 (DE3) - Satrya Pribadi, Raka
Zika virus is an enveloped ssRNA (+) virus belonging to the Flaviridae family. The high similarity of the Zika virus with other members of the Flaviridae family, such as the Dengue Virus and Yellow Fever Virus, often results in patients, infected with the virus, experiencing misdiagnosis and has an effect on prognosis and subsequent treatment errors. Therefore, diagnostic tests that have high specificity are needed to be able to distinguish Zika virus from other Flaviviruses. Previous studies have developed multi-epitope candidates for the Zika virus which are thought to increase the specificity of diagnostic tests on the virus. In previous studies, some amino acid residues from domain I and II of the Zika virus envelope (E) protein were used to develop the multi-epitope protein candidate. However, the multi-epitope protein produced in the study, called ZIKA + L18, still has low solubility, making it difficult for purification and further process. Therefore, in this study, we want to increase the solubility of ZIKA+L18 proteins by using osmolites in the form of sucrose and sorbitol. The study was divided into two main steps, namely the confirmation step for recombinant protein expression confirmation and the optimization step using osmolites in ZIKA+L18 expression. Confirmation step is done by the Polymerase Chain Reaction (PCR) method and the SDS-PAGE method for analyzing recombinant protein expression. Whereas at the optimization stage two osmolites are used, namely sorbitol and sucrose. Osmolites were added to recombinant bacterial culture and incubated for 30 minutes. The incubated culture was then induced using 0.01 mM IPTG at 20 ° C for 20 hours. The sorbitol concentration used was 0.1, 0.3, 0.5; and 0.7 M, while the concentration of sucrose used was 0.1, 0.2, 0.3; and 0.4 M. Cell culture containing ZIKA + L18 protein was then lysed using sonication and then separated between dissolved and nondissolved fractions for protein analysis using the SDS-PAGE method. The SDSPAGE results are then quantified using the ImageJ application. Protein solubility in the treatment group was then compared with the control group, which is the recombinant bacterial culture induced by IPTG but without osmolites. Confirmation results using the PCR method showed that a gene suspected to encode a ZIKA + L18 protein measuring around 883 bp was successfully amplified. The SDS-PAGE results of confirmation and treatment showed that the protein that was thought to contain multi-epitope protein Zika virus was more than 25 kDa than it should be, which was 24 kDa. The results of protein analysis at the optimization stage showed that, in all concentrations, sorbitol could significantly increase recombinant protein solubility. The highest solubility was found in sorbitol with a concentration of 0.5 M. While in optimization using sucrose, there was no ZIKA + L18 protein band. From these results it can be concluded that sorbitol can increase protein solubility, while the effect of sucrose on the solubility of recombinant proteins cannot be determined.